Danger in police culture : perspectives from South Africa - Perkins, Gráinne (Emerald Publishing Limited, 2023)
Danger in Police Culture: Perspectives from South Africa offers a fresh perspective on how officers understand, interpret and construct danger. With unique insight from working with uniformed and detective police, the author breaks new ground as the first researcher to work alongside a Tactical Response Team in South Africa. Through ethnographic research in South Africa, Perkins explores the lived experiences of police navigating danger and death. Reframing the question of what makes policing dangerous, the author employs a theoretical framework as a prism, illuminating ambiguous ideas shaping perceptions of danger in police culture. A vivid portrayal of how danger is materialized through risk reduction strategies and artefacts, dramatized through memorialization and normalized in daily police practices, Perkins concludes by reflecting on policy developments aimed at addressing the understanding and influence of danger in contemporary policing. Underscoring the need to reconsider the concept of danger in policing, this is a much-needed assessment of its understanding and impact on contemporary police work. In support of the Perkins Síochána Scholarship, the author's proceeds from the sale of this book will be used to fund the continuing development of South African graduate students in Criminal Justice and Criminology studies in the Global South.